2022
DOI: 10.3389/fpsyt.2022.900277
|View full text |Cite
|
Sign up to set email alerts
|

Emotional dysregulation as trans-nosographic psychopathological dimension in adulthood: A systematic review

Abstract: IntroductionEmotional dysregulation (ED) is characterized by inappropriate emotional reactions related to environmental or cognitive stimuli. In most recent years, increasing interest has been devoted to its definition and detection across mental disorders for its detrimental role progressively highlighted in both neurodevelopment and adult mental disorders, with implications on the severity of clinical manifestations. The aim of this systematic review was to evaluate and gather the scientific evidence about E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 176 publications
0
10
0
Order By: Relevance
“…It is important to note that the considerations we presented in this section are general and not restricted to clinical population. However, emotion dysregulation is a transdiagnostic risk factor for psychopathology ( 60 , 61 ) and it can be found in a large number of psychiatric disorders ( 8 ). At this point, readers may ask how these processes (i.e., process model of emotion regulation, context-dependent conceptualization of emotion dysregulation…) can be differentially impaired in a way that leads to different categories of psychopathology.…”
Section: How Does Emotion (Dys)regulation Work and Develop?mentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the considerations we presented in this section are general and not restricted to clinical population. However, emotion dysregulation is a transdiagnostic risk factor for psychopathology ( 60 , 61 ) and it can be found in a large number of psychiatric disorders ( 8 ). At this point, readers may ask how these processes (i.e., process model of emotion regulation, context-dependent conceptualization of emotion dysregulation…) can be differentially impaired in a way that leads to different categories of psychopathology.…”
Section: How Does Emotion (Dys)regulation Work and Develop?mentioning
confidence: 99%
“…ED is an integral part of the borderline diagnosis, as emphasized by the presence of the construct and of its related symptoms (NSSI, recurrent suicide attempts, impulsive behaviors, interpersonal conflicts…) in the list of the 9 criteria. In this context, clinicians often associate these symptoms with the BPD diagnosis, and patients with ED often fulfill criteria for BPD, even if it is now well-known that ED can also be encountered in many other psychiatric disorders than BPD, and is currently considered as a transdiagnostic construct (8)(9)(10). In the field of personality pathology, patients suffering from pathological narcissism (PN) (with/without narcissistic personality disorder, NPD), obsessive-compulsive personality disorder (OCPD) and antisocial personality disorder (ASPD) may also present several of the above mentioned symptoms of ED (11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, deficits in ER can be defined as emotion dysregulation (ED), which reflects maladaptive ways during emotion experiences and responses, such as difficulties in emotion understanding or limited access to context-appropriate emotional regulatory strategies (Gratz and Roemer, 2004). Growing evidence from both human behavioral and neuroimaging studies suggest that ED is a trans-diagnostic risk factor as well as the treatment and intervention foci across many mental disorders including ADHD and BD, although it is not included as a formal diagnostic criterion in DSM-5 (American Psychiatric Association, 2013; Carmassi et al, 2022; Kebets et al, 2021; Lenzi et al, 2018). Such as, consistent findings demonstrated that both ADHD and BD patients reported higher ED level and preferred to adopt more maladaptive ER strategies compared to healthy controls (Beheshti et al, 2020; De Prisco et al, 2022; Minò, 2022; Miola et al, 2022; Oliva et al, 2023; Shaw et al, 2014; Soler-Gutiérrez et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, while essential characteristics of ASD, impairments in verbal and nonverbal communication, social functioning, incorrect assumptions about intentions, and emotional outbursts are also frequently documented in BPD subjects ( 33 40 ). Other traits shared by BPD and ASD are a high proportion of self-harming behaviors ( 32 ), pervasive patterns of emotional dysregulation ( 41 , 42 ) and difficulties in the Theory of Mind ( 43 ). On the other hand, to date, the pathophysiology of BPD is still relatively unexplored, and its correlation with ASD is based mainly on the shared clinical and psychological features.…”
Section: Introductionmentioning
confidence: 99%